2020
DOI: 10.1002/jclp.23034
|View full text |Cite
|
Sign up to set email alerts
|

Social engagement, self‐efficacy, and posttraumatic stress symptoms across 6 months of psychotherapy

Abstract: Objective: The current study was conducted in a naturalistic treatment setting to examine whether and how perceptions about social engagement, trauma coping selfefficacy, and posttraumatic stress symptoms (PTS) influence one another across 6 months of psychotherapy for trauma survivors. Method: The sample included 183 clients who reported exposure to traumatic events and significant PTS (PCL-5 ≥ 33). Participants (M age = 37.8, 53.6% female) completed surveys at intake, 3 months, and 6 months into treatment. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 68 publications
(100 reference statements)
0
3
0
Order By: Relevance
“…This resilience-promoting interplay between internal coping appraisals and external social resources is proposed to occur through two mechanisms: (1) social interactions that enable, empower, or improve an individual’s CSE perceptions (i.e., enabling hypothesis), and/or (2) higher CSE beliefs that enhance one’s ability to extract the health-promoting qualities available in social relationships (i.e., cultivation hypothesis, [ 69 ]). Evidence supports the enabling hypothesis in military veterans, community-level collective trauma settings, and among patients in a clinical setting undergoing trauma-focused therapy [ 76 , 79 , 80 ]. Interestingly and particularly relevant to the present study, evidence also supports the cultivation hypothesis among healthcare providers [ 74 ].…”
Section: Enabling and Cultivation Models Of Resiliencementioning
confidence: 90%
See 1 more Smart Citation
“…This resilience-promoting interplay between internal coping appraisals and external social resources is proposed to occur through two mechanisms: (1) social interactions that enable, empower, or improve an individual’s CSE perceptions (i.e., enabling hypothesis), and/or (2) higher CSE beliefs that enhance one’s ability to extract the health-promoting qualities available in social relationships (i.e., cultivation hypothesis, [ 69 ]). Evidence supports the enabling hypothesis in military veterans, community-level collective trauma settings, and among patients in a clinical setting undergoing trauma-focused therapy [ 76 , 79 , 80 ]. Interestingly and particularly relevant to the present study, evidence also supports the cultivation hypothesis among healthcare providers [ 74 ].…”
Section: Enabling and Cultivation Models Of Resiliencementioning
confidence: 90%
“…They are especially important during and after traumatic stress exposures [ 24 , 100 ], with evidence suggesting that they predict recovery in collective/community trauma settings (a traumatic event[s] such as a pandemic or natural disaster that affects an entire people group or society; [see 28, 80, 81]), and are integrally associated with PTSD symptoms over time [ 101 ]. In clinical settings, social support influences patients’ ability to extract benefits from trauma-focused treatments [ 12 , 45 , 58 , 76 ]. Cross-sectional research conducted during the COVID-19 pandemic identified social support as a predictor and buffer of mental health among healthcare workers [ 31 ] and community members [ 43 ], and likely to be involved in development, persistence, and/or resolution of post-pandemic PTSD [ 104 ].…”
Section: Resilience Via the Interplay Of Interpersonal And Intra-indi...mentioning
confidence: 99%
“… Nietlisbach and Maercker (2009) ; A. J. Smith et al (2018) also agree with SCT that understanding trauma adaptation requires an understanding of the relationship between coping self-efficacy, social environments, and psychological distress, especially considering the detrimental social cognitive consequences (social exclusion, isolation, and cynicism) that struggling trauma survivors often experience. Shoji et al (2021) opine that with a sense of security in the post-traumatic environment, social engagement can serve as the cornerstone for fostering coping self-efficacy. Adolphs (2003) defines Social cognition as the collection of neurobiological, psychological, and social processes that enable people to observe, recognize, and assess social events in order to create representations of their interpersonal connections which serve as social behaviour models for them.…”
Section: Theoretical Frameworkmentioning
confidence: 99%